“You can’t speak Creole in here. English only”: Experiences of Stigma and Acts of Resistance among Adults of Haitian Descent in the Bahamas - Perry, Charmane M. (International Journal of Bahamian Studies, 2020)
This article builds upon William J. Fielding, Virginia Ballance, Carol Scriven, Thaddeus McDonald, and Pandora Johnson’s (2008) argument that there is a strong and pervasive stigma of being Haitian in The Bahamas. In this article, I build upon and support their research by using examples from 28 semi-structured interviews with adults of Haitian descent in The Bahamas which reinforce their arguments concerning stigma. In particular, I explore examples of stigma in the public hospital, speaking Haitian Creole, fear of being stopped by immigration officers, and surnames. This article will conclude by discussing the ways people of Haitian descent display acts of resistance in the face of such stigma. This is important because it demonstrates the way people of Haitian descent persevere in the face of adversity and the incessant stigma of being Haitian in The Bahamas.